ESTIMATION OF PROSTATIC SIZE IN DOGS USING TRANSABDOMINAL ULTRASONOGRAPHY - NAIR, DIVYA R; GHOSH, K N ARAVINDA; M HARSHAN, HIRON (The Indian Journal of Animal Reproduction, 2023)
Transabdominal ultrasonog raphic evaluation was carried out to estimate prostatic size in 43 ad ult male dogs of four different breeds. Adult German shepherd dogs had a mean prostatic volume and weight of 26.62±1.58 cm3 and 24.33±1.65 g respectively. The mean prostatic volume and weight in adult Rottweilers were found to be 26.32±2.55 cm3 and 24.01±2.66 g respectively.Among the adult male examined by transabdominal ultrasonography in Dachshund the mean prostatic volume and weight were found to be 13.07±0.96 cm3 and 10.89±0.10 g respectively, while the prostatic volume and weight in case of adult Spitz were observed to be 11.63±0.24 cm3and 8.71 ±0.25g respectively. The study confirmed that age and bodyweight of the animal had a positive correlation with prostatic volume and weight.